CRGD-installed docetaxel-loaded mertansine prodrug micelles: redox-triggered ratiometric dual drug release and targeted synergistic treatment of B16F10 melanoma. (30th June 2017) - Zhong, Ping; Qiu, Min; Zhang, Jian; Sun, Huanli; Cheng, Ru; Deng, Chao; Meng, Fenghua; Zhong, Zhiyuan
Abstract: Combinatorial chemotherapy, which has emerged as a promising treatment modality for intractable cancers, is challenged by a lack of tumor-targeting, robust and ratiometric dual drug release systems. Here, docetaxel-loaded cRGD peptide-decorated redox-activable micellar mertansine prodrug (DTX-cRGD-MMP) was developed for targeted and synergistic treatment of B16F10 melanoma-bearing C57BL/6 mice. DTX-cRGD-MMP exhibited a small size of ca. 49 nm, high DTX and DM1 loading, low drug leakage under physiological conditions, with rapid release of both DTX and DM1 under a cytoplasmic reductive environment. Notably, MTT and flow cytometry assays showed that DTX-cRGD-MMP brought about a synergistic antitumor effect to B16F10 cancer cells, with a combination index of 0.37 and an IC50 over 3- and 13-fold lower than cRGD-MMP (w/o DTX) and DTX-cRGD-Ms (w/o DM1) controls, respectively. In vivo studies revealed that DTX-cRGD-MMP had a long circulation time and a markedly improved accumulation in the B16F10 tumor compared with the non-targeting DTX-MMP control (9.15 versus 3.13% ID/g at 12 h post-injection). Interestingly, mice treated with DTX-cRGD-MMP showed almost complete growth inhibition of B16F10 melanoma, with tumor inhibition efficacy following an order of DTX-cRGD-MMP > DTX-MMP (w/o cRGD) > cRGD-MMP (w/o DTX) > DTX-cRGD-Ms (w/o DM1) > free DTX. Consequently, DTX-cRGD-MMP significantly improved the survival rates of B16F10 melanoma-bearing mice. Importantly, DTX-cRGD-MMP caused little adverse effects as revealed by mice body weights and histological analyses. The combination of two mitotic inhibitors, DTX and DM1, appears to be an interesting approach for effective cancer therapy.